Impedance shaping based stabilization control method for DC Micro-grid Feed-forward compensation - Xiaojuan Zhang; Bo Jing; Yuan Wang; Xiangzhen Meng; Jie Zhang (Scientific Reports)
Abstract The ports of the bi-directional converter exhibit negative impedance characteristics when the energy storage unit of a DC microgrid is operating in charging mode. This can decrease the system’s stability margin, potentially leading to oscillation instability. To address this issue, we propose a feed-forward compensation control method based on impedance shaping. This involves designing a transfer function within the current feed-forward loop of the energy storage converter to ensure that the current reference value follows changes in the bus voltage. Selecting an appropriate time constant ensures that the port impedance of the energy storage unit exhibits a positive resistive characteristic close to the oscillation frequency while retaining a negative impedance characteristic in the low-frequency range. This ensures the stability of system operation. MATLAB/Simulink simulations and RT-LAB semi-physical platform testing have verified that the proposed control method effectively enhances the system’s stability margin, ensuring stable operation and minimal steady-state voltage deviation.